Sexual harassment: The ‘silent killer’ of female students at the University of Ayoba in South Africa - Adams, J.D.; Mabusela, M.S.; Dlamini, E.T. (South African Journal of Higher Education, 2016)
The current non-experimental study sought to establish the extent to which sexual harassment takes place at the institution under investigation, which for reasons of anonymity will be referred to as the University of Ayoba.) The research problem of this study is articulated through the following research questions: (1) What is sexual harassment? (2) Does sexual harassment exist in the University of Ayoba? (3) How is sexual harassment handled at University of Ayoba? The study targeted female fourth year students in the faculty of education. Data were collected by means of a questionnaire and were analysed quantitatively. The findings show that respondents understand what sexual harassment means. The findings furthermore reveal that sexual harassment is prevalent at the case study university; the biggest problem is evident in students who have had to repeat modules due to their refusal of the attentions of sex-seeking lecturers. The results of the study indicate that incidents of sexual harassment are seldom reported adequately by victims, as these would rather be discussed among females. Implications of sexual harassment are discussed and recommendations are made on how to address sexual harassment.